The Value of Symbols in the Works of Potters (Saad Shaker) and (Maher Al-Samarrai): A Comparative Study - محمد, رۆژگار كمال (Sulaimani Journal for Humanities, 2019)
This paper deals with compression of the Pottery art symbols in the Modern-Iraqi symbolized- Pottery hand works of both Iraqi artist Sa'ad Shaker and Maher Al-Samarraii. The paper included three sections; 1.Section one was Contained the problem and aims of the work, and phrases which in turn show the difference and similarity of the symbols in the the aforementioned above artists. 2. Section Two was focused on the theory of the work and it is consisted of three parts, part one; symbolization as a phrase, part two symbolization in in Paleo- Iraqi arts, and part three reflection of symbolization sources in the Modern-Iraqi Pottery. Section Three is the application that includes a. theory of the application, b. research community and examples, c. tool of research and d. analysis and discussion. Section Four deals with the results and the importance. 1. Maher Al- Samarraii; he was an artist, who affected by a number of dialects. The most conspicuous effect can be observe in his research in Neo- Western and familiarity with technology of Pottery, and it connects the culture and current time. 2. The experiences of Maher Al- Samarraii take an especial path through subjectification of objects that tend to wide dialects to assemble a nation due to the concepts of Forms and the value of colours. 3. Maher Al- Samarraii showed relief letters that resembles the holly Quran's, which gives a feel to reader that the artist was affected by Islamic heritage. 4. Sa'ad Shaker is a famous character in the neo- ceramic handcrafts since he was able to use the terms of ethnics and could trespass work limits in ceramics through invention of shapes and way of expression in circle moving. 5. Sa'ad Shaker used diversification in his works, to do this; he used imagine arts and his artistic background, which is enriched with Antiquities,archeology and the heritage elements remains of the Mesopotamia. 6. Sa'ad Shaker was affected by the geometric shapes, but he played with the lines in a manner that they are compatible with his imaginations.